Model of aliphatic polyesters hydrolysis comprising water and oligomers diffusion. (January 2019) - Borovikov, P.I.; Sviridov, A.P.; Antonov, E.N.; Dunaev, A.G.; Krotova, L.I.; Fatkhudinov, T.Kh.; Popov, V.K.
Abstract: The work is dedicated to the development of mathematical models of hydrolysis of aliphatic polyesters in aqueous media under conditions of water and oligomers diffusion. Water molecule is considered as a reagent in hydrolysis reactions, oxidation reactions and influence of the autocatalytic channel are taken into account. The analysis of the spatiotemporal distribution of molecular weight of the polymer depending on the hydrolysis reaction rate constants, the diffusion coefficients of water and short oligomers has been carried out. In case of large water diffusion coefficients, the heterogeneous channel of polymer hydrolysis is actually described by the equation of pseudo-first order, as in most modern models, and occurs predominantly in the volume (V-type). With the decreasing water diffusion coefficient, the participation of water as a reagent becomes very important. The resorption of the polymer occurs mainly near the surface (S-type). The comparison/verification of the developed computer model has been carried out basing on experimental data for molecular weight dynamic of monolithic polylactoglycolide samples (75:25) of different thicknesses in phosphate-buffer saline. The choice of kinetics parameters of hydrolysis reactions and diffusion coefficients of water and oligomers has been justified by fitting of experimental and model data. Graphical abstract: Highlights: Second order hydrolysis reaction is taken into account at diffusion limitation of water. The space-time distribution of the molecular weight is analyzed as function of kinetics parameters. The types of polymer decomposition ("V" or "S") are determined mainly by the diffusion coefficient of water and oligomers. The significant increase of polymer porosity could not be explained just by release of short chains.